2023
DOI: 10.1111/jcpe.13912
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell sequencing identifies inflammation‐promoting fibroblast–neutrophil interaction in peri‐implantitis

Jia‐ji Mo,
Yi‐rao Lai,
Qian‐ru Huang
et al.

Abstract: AimTo reveal the cellular composition and molecular environment of the periodontal and peri‐implant inflammatory infiltrates through a single‐cell sequencing technique, which may explain the pathological difference between these two diseases. A special focus was placed on the phenotypes and potential roles of neutrophils and fibroblasts in peri‐implant/periodontal tissue immunity.Materials and MethodsHigh‐throughput single‐cell transcriptomic profiling of peri‐implant tissues from patients with peri‐implantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…An increase of polymorphonuclear leukocytes (PMN) in peri-implant tissue is considered a significant indicator of inflammation, which could lead to mucositis and peri-implantitis (Berglundh et al, 2018; Schwarz et al, 2018). A single-cell sequencing study supports the involvement of PMNs in inflammation, as it has shown elevated levels of CXCL8, a PMN-attracting cytokine, in peri-implant tissue [ 31 ]. Therefore, the presence of PMNs and their association with inflammation could indicate an association with the pathogenesis of peri-implant diseases [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase of polymorphonuclear leukocytes (PMN) in peri-implant tissue is considered a significant indicator of inflammation, which could lead to mucositis and peri-implantitis (Berglundh et al, 2018; Schwarz et al, 2018). A single-cell sequencing study supports the involvement of PMNs in inflammation, as it has shown elevated levels of CXCL8, a PMN-attracting cytokine, in peri-implant tissue [ 31 ]. Therefore, the presence of PMNs and their association with inflammation could indicate an association with the pathogenesis of peri-implant diseases [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8 is more than an inflammatory cytokine, as it is expressed in healthy periodontal tissues, suggesting its involvement in the permanent need for the periodontium to defend against the microbial burden of the oral cavity [ 10 ]. Moreover, once homeostasis shifts into the pathological stage, CXCL8 becomes a marker of periodontitis [ 8 , 9 , 10 ] and periimplantitis [ 11 ]. The fibroblasts are the primary producers of CXCL8 in periodontitis tissues [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8 expression is a double-edged sword: (i) it supports local immunity being constantly expressed at a low level, (ii) or at transient higher levels during wound healing, (iii) however, when chronically expressed at high levels, CXCL8 becomes a key mediator associated with pathological inflammation and overaccentuated neutrophil recruitment and degranulation, overall causing tissue damage [ 7 ]. It is, therefore, not surprising that in healthy periodontal tissues, CXCL8 is regularly expressed to control tissue homeostasis, but CXCL8 is increasingly expressed in the pathological conditions of periodontitis [ 8 , 9 , 10 ] and periimplantitis [ 11 ]. Importantly, evidence suggests that fibroblasts are the primary source of CXCL8 in periodontitis [ 10 ] and periimplantitis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation